2017
DOI: 10.18203/2320-1770.ijrcog20173467
|View full text |Cite
|
Sign up to set email alerts
|

First versus second stage caesarean section: a comparison of maternal and neonatal outcomes

Abstract: Background: A retrospective study was done to compare the maternal and neonatal complications of caesarean delivery performed in the second stage compared with the first stage of labor.Methods: This is a one year retrospective study done in a 100-bedded hospital, govt of NCT OF Delhi, New Delhi from 1st November 2015 to 31st October 2016.  Total number of deliveries in this one year duration were 1785, including both normal and caesarean deliveries. Total number of patients who underwent caesarean delivery in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…In agreement with our findings, previous studies 13 22 showed a significant association between the second stage of CD and neonatal morbidity, including an increased incidence of fifth min Apgar score <7 and higher NICU admission rates, but failed to show an association with neonatal death. In disagreement, our findings show that the CD performed at the second stage of labour is not only associated with neonatal morbidity but also with neonatal mortality, in line with other studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with our findings, previous studies 13 22 showed a significant association between the second stage of CD and neonatal morbidity, including an increased incidence of fifth min Apgar score <7 and higher NICU admission rates, but failed to show an association with neonatal death. In disagreement, our findings show that the CD performed at the second stage of labour is not only associated with neonatal morbidity but also with neonatal mortality, in line with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…The increased amount of blood loss because of uterine atony and unintentional uterine extensions is frequent in the second stage CD, as revealed in the present and previous studies. 13 14 Other studies also showed that unintended uterine extension was associated with longer operation time, more blood loss, postpartum anaemia, and an increased need for blood transfusion. 15 16 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Total number of patients who underwent caesarean delivery in first stage of labour are 400 and in second stage are 130 during the study period. These were categorized as Group-1: CD in first stage of Labour (n=400) Group-2: CD in second stage of Labour (n=130) These two groups were then compared in terms of maternal demographics, labour characteristics, maternal outcomes and neonatal outcomes Numerical variables were compared between groups by calculating p value for each variables and value <0.05 was taken as statistically significant [9,10,11] . Women delivered by Caesarean Section at full dilation have a higher risk of postpartum hemorrhage, operative morbidity with visceral injury, sepsis and prolonged hospital stay.…”
Section: Materials and Methodologymentioning
confidence: 99%